Identification of Seagrass Types and Density in Mibi Village, Makbon District, Sorong, Southwest Papua - Loupatty, Ellen; Fahrizal, Ahmad; Ratna, Ratna; M. Amir Suruwaky; Darwin K. Inggamer (Universitas Islam Lamongan, 2025)
The study was conducted in Mibi Village, Makbon District, Sorong Regency, Southwest Papua, to identify seagrass species and assess their density. The study was conducted in May-June 2024 during low tide using the line transect method with certain stations and repetitions. The results identified seven types of seagrasses, with Halodule uninervis and Syringodium isoetifilium having the highest density. Suggestions for further research include exploring the economic value of seagrass through tourism, fisheries, pharmaceutical, and other industrial sectors, potentially providing a positive impact on the Mibi Village community. This study can be a reference for thesis research or further studies on seagrass in Southwest Papua, Indonesia.